Sarcoid‐Like Reaction (SLR) Associated With Immune Checkpoint Inhibitors in Metastatic Renal Cell Carcinoma - Kanta Fukushima; Sota Mizukoshi; Tomohiro Ino; Takuya Ishida; Yumika Ito; Akira Okimura; Munehide Nakatsugawa; Takeshi Hashimoto (IJU Case Reports)
ABSTRACT Introduction Immune checkpoint inhibitors (ICIs) are useful in the treatment of metastatic renal cell carcinoma. ICIs have been associated with a variety of immune‐related adverse events (irAEs), one of which is a sarcoid‐like reaction (SLR). SLR is often difficult to distinguish from cancer progression. Case Presentation The patient is a 71‐year‐old woman. She underwent laparoscopic nephrectomy after 4 courses of ipilimumab + nivolumab therapy for clear cell renal cell carcinoma with femoral bone metastasis. In the pathological examination, in addition to tumor‐infiltrating lymphocytes, numerous non‐caseating epithelioid cell granulomas were found in the tumor. The occurrence of non‐caseating epithelioid cell granuloma in a patient who did not meet the diagnostic criteria for systemic sarcoidosis was considered SLR due to ICI. Conclusions We report the first case of a patient who underwent surgery for metastatic renal cell carcinoma after treatment with ICI and who was pathologically diagnosed with SLR in the kidney.